Implementasi Program KKN untuk Peningkatan Visibilitas UMKM Desa Tanah Merah Kabupaten Serdang Bedagai melalui Google Maps - Ridho Feriyanly; Siska Safitri; Devi Tri Saputri Manik; Zainarti Zainarti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
The Community Service Program (KKN) in Tanah Merah Village, Serdang Bedagai Regency, aims to enhance the visibility of Micro, Small, and Medium Enterprises (MSMEs) by utilizing Google Maps as a digital promotional tool. In this village, many MSMEs face challenges due to low digital literacy, which hinders their ability to leverage technology for marketing their products. Through the KKN program, students conducted surveys, initial socialization, and hands-on training on using Google Maps and Google Business Profile for MSME owners. The results show that MSME owners gained a better understanding of digital marketing, especially in using Google Maps. They experienced significant benefits from the easy access it provided for consumers to find their business locations, leading to an increase in customers. Additionally, using Google Business Profile helped boost their credibility among consumers. This KKN program plays a crucial role in empowering MSMEs to adapt to digital technology, expand their market reach, and enhance their business competitiveness. With this support, MSMEs in Tanah Merah Village are now capable of managing their business profiles independently and are better prepared to face the challenges of an increasingly digital market.